Unexpected Recovery Risk and LGD Discount Rate Determination - Jiří Witzany (European Financial and Accounting Journal, 2009)
The Basle II parameter called Loss Given Default (LGD) aims to estimate the expected losses on not yet defaulted accounts in the case of default. Banks firstly need to collect historical recovery data, discount the recovery income and cost cash flow to the time of default, and calculate historical recovery rates and LGDs. One of the puzzling tasks is to determine an appropriate discount rate which is very vaguely characterized by the regulation. This paper proposes a market consistent methodology for the LGD discount rate determination based on estimation of the systematic, i.e. undiversifiable, recovery risk and a cost of the risk.
Keywords: C14; G21; G28; 650; Credit risk; Recovery rate; Loss given default; Discount rate; Regulatory capital